Determinants of Dairy Plants Location: An Empirical Study - Turka, Suresh Kumar; Sharma, Tejinder (Gyan Management Journal, 2010)
The issue of site selection is important for all the industries, irrespective of their nature. Be it manufactun’ industry, agro based industry, service outlet, wholesale or retail store, location is an important consideratic·" not only from the operational aspects, but also from the strategic perspective. Most other variables of a strate